ANALISIS SINYAL TANGAN MILITER DALAM FILM AMERIKA BLACK HAWK DOWN - LONGDONG, JEINNEFER CAIRIANY (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT In this research the writer investigates military hand signals in American film Black Hawk Down. This study is an attempt to identify, classify, and analyze the hand signals produced by the soldiers in film Black Hawk Down. The data were collected from the film Black Hawk Down. All the collected data, were analyzed by using the classification of Joseph Terry (2014), and descriptive method of John Best (1982). The results of this research show that there are six forms of hand signals by the soldiers and their meanings that appear during the film. The first one is fist which means stop or freeze. The second one is numbers of finger pointing by the air which means noticing the time. The third one is pointing with index finger which means indicating direction. The fourth one is thumbs up which means good condition. The fifth one is finger pointing at the recipient which means giving order to someone. The last one is index finger pointing up and making a circle above the shoulder which means commanding to gather. The writer also finds three other forms, and its meanings which are not listed in Terry’s (2014) classification. The first one is casting the hand which means ordering to go. The second one is clenching the five fingers which means ordering to distract. The last one is opening the index finger and thumbs which means taking over the opponent’s weapon. Keywords: Military Hand Signals, American Film Black Hawk Down